Posterior corneal vesicles are not associated with the genetic variants that cause posterior polymorphous corneal dystrophy - Liskova, Petra; Hafford-Tear, Nathaniel J; Skalicka, Pavlina; Malinka, Frantisek; Jedlickova, Jana; Ďuďáková, Ľubica; Pontikos, Nikolas; Davidson, Alice E; Tuft, Stephen (Acta ophthalmologica, 2022)
PURPOSE: Posterior corneal vesicles (PCVs) have clinical features that are similar to posterior polymorphous corneal dystrophy (PPCD). To help determine whether there is a shared genetic basis, we screened 38 individuals with PCVs for changes in the three genes identified as causative for PPCD. METHODS: We prospectively recruited patients for this study. We examined all individuals clinically, with their first-degree relatives when available. We used a combination of Sanger and exome sequencing to screen regulatory regions of OVOL2 and GRHL2, and the entire ZEB1 coding sequence. RESULTS: The median age at examination was 37.5 years (range 4.7-84.0 years), 20 (53%) were male and in 19 (50%) the PCVs were unilateral. Most individuals were discharged to optometric review, but five had follow-up for a median of 12 years (range 5-13 years) with no evidence of progression. In cases with unilateral PCVs, there was statistically significant evidence that the change in the affected eye was associated with a lower endothelial cell density (p = 0.0003), greater central corneal thickness (p = 0.0277) and a steeper mean keratometry (p = 0.0034), but not with a higher keratometric astigmatism or a reduced LogMAR visual acuity. First-degree relatives of 13 individuals were available for examination, and in 3 (23%), PCVs were identified. No possibly pathogenic variants were identified in the PPCD-associated genes screened. CONCLUSION: We found no evidence that PCVs share the same genetic background as PPCD. In contrast to PPCD, we confirm that PCVs is a mild, non-progressive condition with no requirement for long-term review. However, subsequent cataract surgery can lead to corneal oedema.
Keywords: rohovka; Corneal Dystrophies, Hereditary; corneal endothelium; Humans; lidé středního věku; dítě; Corneal Edema; Transcription Factors; Child; Female; Aged; mladý dospělý; dospělí; cornea; senioři; dědičné dystrofie rohovky; lidé; OVOL2; edém rohovky; astigmatismus; předškolní dítě; Adult; Cornea; ZEB1; ženské pohlaví; Male; GRHL2; Middle Aged; Adolescent; Aged, 80 and over; Young Adult; senioři nad 80 let; transkripční faktory; mužské pohlaví; Child, Preschool; Astigmatism; mladiství